Corrector problem in the deterministic homogenization of nonlinear elliptic equations. Issue 1 (25th January 2019) - Cardone, Giuseppe; Woukeng, Jean Louis
ABSTRACT: We carry out the deterministic homogenization of nonlinear elliptic operators beyond periodicity. To proceed with, we prove the existence of nonlinear correctors in the usual distributional sense. This lays the foundation for the study of regularity results in the nonlinear deterministic homogenization theory beyond the periodic setting.